L’Assurance en l’an 2000. Évolution ou métamorphose - Gumbel, Edward (Assurances)

(untitled) (HEC Montréal, 1992)
Several years ago, Mr. Edward Gumbel, a distinguished British personality in the field of insurance and reinsurance, presented a detailed analysis of the English market at the Centre Européen de l'Assurance de Saint-Gall. We are pleased to publish this study which was recently revised by the author at the request of our French counterpart, L’Assurance française, to whom we are grateful for allowing us to reproduce this article.